Future of legal education in Malaysia: towards a common bar course - Ramalingam, Chithra Latha; Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
The origins and the development of legal education and its profession in Malaysia lend its backdrop by the sponsors of the colonisation period in Malaysia.2 It is not known exactly when the legal profession was first introduced in England because prior to the 12th century3 the idea of courts generated from the local property ownership system where there were obligations of the people to the owners known as Lords which they occupied. Therefore, law and courts were practised according to the customary practises of the area or known as county.4 This shows that the legal profession per se at that time did not exist as how it is now practised.